A Survey on Blockchain-Based Routing in Communication Networks - Wijesekara, Patikiri Arachchige D.S.N. (IAES Indonesian Section, 2025)
Routing in communication networks involves the transmission of packets among network nodes by making routing decisions constructed upon diverse protocols that can depend on various metrics. Blockchain systems made up of concatenated blocks inherently preserve the faithfulness, assure the non-deniability, and assure the obscured individuality of their transactions/blocks through the incorporation of distributed unanimity mechanisms and cryptographic techniques. In the present literature, it clearly lacks a review manuscript on the broad scope of blockchain-based routing; thus, we fill that gap by studying Blockchain-based Routing (BBR) under numerous routing techniques, identifying the concept under 5 divisions, and then in-depth scrutinizing the reviewed work based on blockchain-correlated, routing-correlated, and network-correlated characteristics. We collected a premature sample of 83 articles by cherry-picking articles for qualification requirements explored in scientific databases, employing an in-depth and extended quality assessment approach. As per the appraisal, BBR improves the overall routing performance and security through the storage of routing decisions and updates securely, automatic routing with the aid of smart contracts, providing authentication for secure routing, providing reputation-based routing, and blockchain-based onion routing. In-depth scrutinization reveals that 45.5% of BBR frameworks utilize blockchain for storing routing decisions and updates; 93.2% employ linear blockchain architecture; 20.5% employ proof-of-work consensus; 100% dynamic routing; 72.8% decentralized routing; 93.2% single path routing; 86.4% table-based; and 20.5% are designed for IoT networks. Finally, we disclose the possibilities and impediments of the idea of BBR, identify review gaps, and then render proposals to conquer them.